Conceptualization and measurement of key account management orientation - Spiros Gounaris; Nektarios Tzempelikos (jbm - Journal of Business Market Management, 2012)
Even though the importance of Key Account Management (KAM) in building long term buyer-seller relationships is widely recognized in literature this long term perspective of KAM lacks appropriate empirical examination. The purpose of this study is to propose a conceptualization of Key Account Management Orientation (KAMO) as well as to derive an empirical based measure of it. In doing so, we first establish the construct through qualitative research and then using quantitative data from 304 personally administrated interviews we examined the psychometric attributes of the proposed construct. A set of attitude-related and behavior-related dimensions emerge from the study which aggregate to KAMO as a higher-order construct.
urn:nbn:de:0114-jbm-v5i3.222
Keywords: 650; key account management; empirical study; business-to-business marketing; Key-Account Management; B-to-B-Marketing; Faktorenanalyse